2006
DOI: 10.1002/jemt.20326
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and reliable in vitro method combining scanning electron microscopy and image analysis for the screening of osteotropic modulators

Abstract: The increased generation and up-regulated activity of bone resorbing cells (osteoclasts) play a part in the impairment of bone remodeling in many bone diseases. Numerous drugs (bisphosphonates, calcitonin, selective estrogen receptor modulators) have been proposed to inhibit this increased osteoclastic activity. In this report, we describe a pit resorption assay quantified by scanning electron microscopy coupled with image analysis. Total rabbit bone cells with large numbers of osteoclasts were cultured on den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The resorption activity of osteoclasts isolated from total RBC preparations was evaluated by the calculation of resorbed surface area on dentin slices, as described previously (Grimandi et al, 2006). To investigate the anti-resorptive activity of Ga, graded concentrations of Ga (from 0-100 mM) was incubated in 24-multiwell culture plates containing one dentin slice per well.…”
Section: Resorption Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The resorption activity of osteoclasts isolated from total RBC preparations was evaluated by the calculation of resorbed surface area on dentin slices, as described previously (Grimandi et al, 2006). To investigate the anti-resorptive activity of Ga, graded concentrations of Ga (from 0-100 mM) was incubated in 24-multiwell culture plates containing one dentin slice per well.…”
Section: Resorption Assaymentioning
confidence: 99%
“…For this purpose, we used the unfractioned RBC model as a well-established culture system that supports the activity of mature resorbing osteoclasts (Grimandi et al, 2006). In this model, the functional activity of osteoclasts was evidenced by a resorption assay showing numerous typical resorption pits on the surface of dentin slices.…”
Section: Gallium Modulates Osteoclastic Bone Resorption E Verron Et Almentioning
confidence: 99%
“…Numerous studies proposed the use of scanning electron microscopy [24][25][26], confocal microscopy [27] and vertical scanning profilometry [28], however most techniques are either time consuming or require specialized instrumentation. In this study, we demonstrated that the measurements of the resorption volume per pit can be simplified on the fluorescently labeled hydroxyapatite substrates, and developed a convenient protocol to estimate the resorption volume using the fluorescence microscopy without the confocal capability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to perform 3D measurement of resorption pits by using various engineering techniques such as scanning electron microscopy, confocal microscopy, and atomic force microscopy (AFM). [11][12][13][14][15][16] Recently, a few in vitro studies of osteoclastic bone resorbing activity have been performed by 3D measurement of resorption pits formed by osteoclasts cultured during short period. [15][16] However, the life span of osteoclasts in vivo appears to be up to 7 weeks, with a half life of around 6 to 10 days 17 , suggesting that formation of resorption pits by osteoclasts and their resorptive activities can be continuously changed with time.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Recently, a few in vitro studies of osteoclastic bone resorbing activity have been performed by 3D measurement of resorption pits formed by osteoclasts cultured during short period. [15][16] However, the life span of osteoclasts in vivo appears to be up to 7 weeks, with a half life of around 6 to 10 days 17 , suggesting that formation of resorption pits by osteoclasts and their resorptive activities can be continuously changed with time. Understanding the changes in osteoclastic resorption activity (volume, depth, and area) in a temporal manner will help to accurately evaluate their effects in vivo and develop new cytokines and drugs to regulate bone resorption.…”
Section: Introductionmentioning
confidence: 99%